Enhancing Olive Production in Mediterranean Agrivoltaic Systems: A Microclimatic Analysis Using Computational Fluid Dynamics Modeling - Elisa Gatto; Leonardo Beccarisi; Barnaba Marinosci; Caterina Polito; Cristiano Tamborrino; Arcangelo Taddeo; Massimo Monteleone (AgriVoltaics Conference Proceedings)
Agrivoltaic Systems (AVs), combining agriculture and solar power generation, represent a sustainable land use method. This research is conducted for the “Borgo Monteruga” agrivoltaic project, located in Southern Italy. The project is characterized by the inter-cropping of high-density olive groves, arranged in hedgerows between solar trackers, with fodder crops on either side or, alternatively, medicinal crops, depending on the soil quality. The park boasts a peak power capacity of 291.33 MWp, achieved through the installation of double-sided 600 W photovoltaic modules and a 50 MW storage system. The novelty of this project lies in the proactive assessment of microclimatic parameters to optimize the AVs layout, aiming to reduce shading on crops and enhance the efficiency of both agricultural and solar energy production. The photovoltaics modules in AVs significantly impacts the local microclimate, influencing aspects such as solar radiation, air and soil temperatures, wind speed, and groundwater retention. Understanding these microclimatic shifts is essential not only for the effective management of AVs and strategic crop selection but also for choosing optimal adaptive solutions to climate change. Additionally, this knowledge is key to establishing a tailored monitoring system with innovative and targeted strategies, ensuring the AVs resilience and productivity in the face of evolving environmental conditions. This study sets a new benchmark in AVs design and optimization by implementing advanced computational fluid dynamics (CFD) modeling for its microclimatic analysis, thereby contributing significantly to the field of sustainable agricultural practices.